Elevated Cardiovascular Risk Factors in Multiple sclerosis patients - النامس معاذ; هالة سعيد; أكرم جحجاح (Latakia University Journal -Medical Sciences Series, 2022)
Background and Purpos . Multiple sclerosis occupies the first place among the neurological diseases that cause disability in young people, as significant motor deficits occur in 30% of them within 20-25 years.. MS patients suffer from decreased physical activity and motor ability, and a sedentary lifestyle: increased risk of cardiovascular disease (CVD). Thus it is important to know and control the cardiovascular risk factors in these patients; To improve the survival rate.. Methods The study included 68 patients with multiple sclerosis who were monitored in the Department of Neurology at Tishreen University Hospital 2019-2020. The patients’ ages ranged between 16 and 48 years, with a mean age of 32.6 ± 8.6 years. Cardiovascular risk factors were investigated in the study patients and then compared with a control group similar in terms of age and sex, consisting of 52 healthy people. The comparison was made between the two groups in terms of smoking, alcoholism, family history and continuous variables: systolic and diastolic pressure, BMI, total cholesterol, triglycerides, HDL and LDL. We divided patients with multiple sclerosis into two age groups, depending on the median age, which is 33 years, and then compared the previous variables between the two groups. A comparison was made between smoking and the degree of disability in a sample of patients. Results It was found that both hypercholesterolemia, low HDL and weight gain were statistically significantly higher in the multiple sclerosis group compared to the control group. It was found that total cholesterol disturbance and weight gain were statistically significantly higher in the age group >33 years compared to younger patients. The degree of disability was found to be statistically significantly higher in smoking patients. Conclusions Dyslipidemia and weight gain are a cardiovascular risk factor in patients with multiple sclerosis The degree of motor disability increases in patients who smoke.